Swastika Dry Cleaning Coal Plant
Swastika Dry Cleaning Coal Plant
Black and White photograph
Master list item #: 2
File location is in the Raton file Cabinet
Keywords: Swastika Mine; Mine Photographs; NM Photographs; Brilliant, NM; Swastika, NM